Metamorphosis of public administration and law in India: A critical assessment of the impact of IT and global competitiveness - Rattan, Jyoti; Rattan, Vijay (2008)
Forces of globalisation and information and communication technologies and the increasing aspirations and expectations of the knowledge society citizens of the 21st Century are bringing about a metamorphosis of public administration into a new entity in India that is more transparent, corruption free, efficient and citizen-friendly in terms of governance. In such a scenario, the metamorphosis of law and the justice delivery system has also begun at a rapid speed. Such a technology-led metamorphosis of public administration and law, despite the usual initial hiccups - that seems to have begun slowly but surely spreading at a faster pace, ferrying information across organizations, systems, and devices at lightening speed, evolving newer and more efficient administrative structures, processes and ways of working for reaching its clientele, and by accident or design. - Reproduced.
Keywords: Globalization - India; Administrative law - India; Public administration - India; Public administration